2022
DOI: 10.1371/journal.pone.0277805
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial susceptibility of Staphylococcus aureus in dairy farms and personnel in selected towns of West Shewa Zone, Oromia, Ethiopia

Abstract: Staphylococcus aureus is one of the foodborne disease-causing bacterial pathogens. A cross-sectional study was conducted in selected towns of the West Shewa Zone, Oromia, Ethiopia from December 2020 to April 2021. The objectives of the study were to estimate the occurrence and load of S. aureus in raw cows’ milk, the antimicrobial susceptibility patterns of the S. aureus isolates, and assess the knowledge, attitude, and practice of the farmers on factors of antimicrobial resistance. A total of 311 samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…In this study, the mean log 10 CoPS for raw milk, yogurt, and cottage cheese were 4.6, 3.8, and 3.2 log 10 CFU/mL, respectively. Similar findings were reported in previous studies conducted in Ethiopia [ 43 , 61 ] and Tanzania [ 62 ] for milk and milk products. However, our results differed from previous studies that reported higher CoPS levels in raw milk in Ethiopia [ 11 , 63 ] and Zimbabwe [ 61 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the mean log 10 CoPS for raw milk, yogurt, and cottage cheese were 4.6, 3.8, and 3.2 log 10 CFU/mL, respectively. Similar findings were reported in previous studies conducted in Ethiopia [ 43 , 61 ] and Tanzania [ 62 ] for milk and milk products. However, our results differed from previous studies that reported higher CoPS levels in raw milk in Ethiopia [ 11 , 63 ] and Zimbabwe [ 61 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported in previous studies conducted in Ethiopia [ 43 , 61 ] and Tanzania [ 62 ] for milk and milk products. However, our results differed from previous studies that reported higher CoPS levels in raw milk in Ethiopia [ 11 , 63 ] and Zimbabwe [ 61 ]. According to the European Commission’s microbiological criteria for dairy products, raw cow’s milk intended for direct human consumption is considered satisfactory if S. aureus counts in all samples does not exceed 500 CFU/mL.…”
Section: Discussionsupporting
confidence: 91%
“…Staphylococcus aureus is a major zoonotic pathogen that not only produce large economic losses in dairy animal production but also poses a risk to public health (Zhou et al, 2017).Staphylococcus aureus is a well-known opportunistic bacterium that can infect dairy animals as well as people. It is the third most prevalent causes of foodborne illness globally (Banu et al, 2022).The bacterium is a frequent colonizer and is thought to be a part of the natural commensal flora of people and animals, colonizing about 30-50% of the human population (Dweba et al, 2018). In humans, S. aureus colonizes the skin and nasal passages.…”
Section: Introductionmentioning
confidence: 99%
“…A number of milk-borne epidemics and outbreaks, such as diphtheria, dysentery, typhoid, etc., have occurred through the consumption of milk and its products by humans [2]. The presence of food pathogens like Staphylococcus aureus, Salmonella spp., Listeria monocytogenes, and Escherichia coli in milk and milk products is responsible for food-borne infections ranging from mild to serious cases, even leading to death [3]. Additionally, AMR among these food pathogens is on the rise [3][4][5] and has resulted in an increased number of hospitalizations, which in turn has increased morbidity and mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of food pathogens like Staphylococcus aureus, Salmonella spp., Listeria monocytogenes, and Escherichia coli in milk and milk products is responsible for food-borne infections ranging from mild to serious cases, even leading to death [3]. Additionally, AMR among these food pathogens is on the rise [3][4][5] and has resulted in an increased number of hospitalizations, which in turn has increased morbidity and mortality [6]. According to the WHO, at least 700,000 people die each year due to drug-resistant diseases, which could escalate to 10 million deaths per year by 2050 [7].…”
Section: Introductionmentioning
confidence: 99%